1981
DOI: 10.1097/00000658-198106000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention in Chronic (Hashimotoʼs) Thyroiditis

Abstract: The incidence of chronic (Hashimoto's) thyroiditis in surgical specimens is relatively high, i.e., 13% in collected studies, for a disease with clinical and laboratory characteristics that are sufficiently specific, that thyroidectomy should rarely be required for diagnosis or treatment. This incidence is presumably related to the difficulty in distinguishing between thyroiditis and a thyroid neoplasm. Experience with 260 thyroidectomies at the North Carolina Memorial Hospital performed between 1875 and 1980 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…Similar study was conducted by Thomas and Rutledge [24] who reported a 3% incidence of HT in their case series operated for nodular goiter and in whom the indications of surgery for HT were narrower. The comprehensive list of indications for surgery in HT based on this study and related review of the literature is as follows: 1) Dominant nodule or large solitary thyroid nodule (>3 cm) 2) Large MNG (>3 cm/retrosternal extension) 3) Compressive symptoms 4) Proven or suspicious associated malignancy 5) Persistent goiter not responsive to full-dose thyroxine replacement 6) Associated Graves' disease (Hashitoxicosis) 7) Painful thyroiditis 8) Incisional biopsy for suspicious lymphoma 9) Cosmetic reasons 10) Patient's wishes…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar study was conducted by Thomas and Rutledge [24] who reported a 3% incidence of HT in their case series operated for nodular goiter and in whom the indications of surgery for HT were narrower. The comprehensive list of indications for surgery in HT based on this study and related review of the literature is as follows: 1) Dominant nodule or large solitary thyroid nodule (>3 cm) 2) Large MNG (>3 cm/retrosternal extension) 3) Compressive symptoms 4) Proven or suspicious associated malignancy 5) Persistent goiter not responsive to full-dose thyroxine replacement 6) Associated Graves' disease (Hashitoxicosis) 7) Painful thyroiditis 8) Incisional biopsy for suspicious lymphoma 9) Cosmetic reasons 10) Patient's wishes…”
Section: Discussionsupporting
confidence: 73%
“…We had high HT incidence of 22.8% among cases operated for goiter compared with many surgical series, which range from 3% to 33% [21,24,25]. Schlicke [21] reported a similar incidence of 23% of HT amongst 713 operated cases of nodular goiter, although from a different geographic zone.…”
Section: Discussionmentioning
confidence: 73%
“…Its treatment is symptomatic and based on the administration of synthetic thyroxine to correct the hypothyroidism when present and/or to decrease thyroid volume by lowering serum thyrotropin concentrations. In contemporary practice, pathology is rarely needed to establish a diagnosis of Hashimoto's thyroiditis, and surgery is seldom used as a form of treatment (29)(30)(31). Yet, analysis of surgical pathology records over a prolonged period of time provides insights about the natural history of the disease, as well as the practice of medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HT are usually treated conservatively with levothyroxine (L-T4) therapy in an attempt to decrease thyroid volume and supplement thyroid hormone 5,11,12 . However, there are certain circumstances in which patients with HT are referred for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are certain circumstances in which patients with HT are referred for surgery. In general, the indications for surgery in HT patients include suspicion of malignancy, persistent symptoms associated with the disease, or a goiter that is increasing in size 5,1315 .…”
Section: Introductionmentioning
confidence: 99%